Analisis Pengaruh Orientasi Kewirausahaan dan Kemandirian Operasional terhadap Kinerja Usaha UMKM Kuliner Seblak Kecamatan Parungponteng Kabupaten Tasikmalaya - Gina Fadilah; Ucu Supriatna (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the effect of Entrepreneurial Orientation (X1) and Operational Independence (X2) on Business Performance (Y) of Seblak UMKM in Parungponteng District. The population was 60 business actors using total sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed: (1) X1 has a positive significant effect on Y (t=6.611 > 1.984; sig 0.000); (2) X2 has a positive significant effect on Y (t=2.569 > 1.984; sig 0.013); (3) X1 and X2 simultaneously have a significant effect on Y (F=60.821 > 3.09) with a contribution of 68.1% (R²=0.681). In conclusion, increasing entrepreneurial orientation and operational independence can improve UMKM performance. The main suggestion for business owners is to enhance proactive attitudes and operational initiative.